Efektivitas Analgesik Kombinasi Parasetamol dan Ekstrak Kasar Nanas terhadap Refleks Geliat Mencit yang Diinduksi Asam Asetat (The Analgesics Effectivity of Combination of Paracetamol and Pineapple Crude Extract on Writhing Reflex in Mice Induced by Ace - Fauqi Amalia; Cholis Abrori; Ika Rahmawati Sutejo (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Bromelain is a proteolytic enzyme which can be found in pineapple. The proteolytic activity of bromelain commonly used as an anti-inflammatory agent and antioedema, antithrombotic, and fibrinolytic agent. This study aimed at determining the combination effectivity of paracetamol and bromelain, pineapple crude extract’s protein, on pain response in mice and its interaction. This research used true experimental design with posttest only control group. Data analysis using Kruskal-Wallis test and application CompuSyn. The mice induced by acetic acid as the pain’s trigger and writhing reflex calculated every 5 minutes for 1 hour. The results of this study were expressed by pain protection persentage of paracetamol, crude extract of pineapple, a combination dose of paracetamol and crude extract of pineapple ½:½ and 1:1 was 52.23 ± 3.94%; 51.28 ± 6.71%; 77.88 ± 4.02%; and 71.24 ± 10.54%. The results of the CompuSyn dose combination analysis showed a synergistic effect that is seen from the CI value. In conclusion, analgesic effectivity combination of paracetamol and pineapple crude extract more effective than single dose usage and showed a synergistic effect. Keywords: analgesic, bromelain, pain, paracetamol, pineapple